Effect of Copper-Doping on LiNiO2 Positive Electrode for Lithium-Ion Batteries. Issue 14 (18th November 2020) - Kong, Xiang-Ze; Li, Dong-Lin; Lahtinen, Katja; Kallio, Tanja; Ren, Xu-Qiang
Abstract : LiNiO2 (LNO) is one of the most potential alternatives to LiCoO2 in Li ion batteries (LIBs). However, it still suffers from poor cyclability. Meanwhile, the recycling processes of LIBs are widely investigated to enable effective recycling for the growing amounts of LIB waste. Cu is one of the dominating impurities in LIB recycling fractions. In this work, LNO and 0.2 mol% Cu-doped LNO are studied. Cu-doping is demonstrated to stabilize the LNO lattice structure, reduce cation mixing and improve the reversibility of phase transitions during electrochemical processes. Consequently, the rate capability of LNO is improved by Cu-doping, especially at high C-rates. The Cu-doped LNO shows much higher capacity retention of 85% than that of 66% for the undoped LNO at the current density of 100 mA·g −1 after 100 cycles in a voltage window of 2.5–4.5 V. Our results show that a possible Cu contamination in the Ni fraction of the LIB material recovery process can be used to enhance the electrochemical properties of newly synthetized Ni-based positive electrode materials.